2018
DOI: 10.5424/sjar/2017154-11507
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an antioxidant system in tolerant and susceptible wheat seedlings in response to salt stress

Abstract: It has been demonstrated previously that the physiological and molecular analysis of seedlings of the tolerant (Om Rabia3) and susceptible (Mahmoudi) Tunisian wheat genotypes were different at short and long-term response to salinity. In this study, we examined the antioxidant defence system in seedlings of these two cultivars at short-term response to different NaCl concentrations. The findings showed that high salinity tolerance of cv. Om Rabia3, as manifested by lower decrease in its dry biomass, was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 64 publications
6
12
0
Order By: Relevance
“…In 'R18', 'R19', 'R23' and 'R30', the most elevated salt concentration (160 mM NaCl) generated the highest CAT activity, thus leading to improved protection against ROS in all the regenerated plants. This result agrees with previous reports, stating that many salt-tolerant species exhibited higher CAT activity, such as maize [136], sesame [137], potato [138], melon [139] and wheat [140]. Several earlier authors reported that salinity increased APX activity in many salt-tolerant cultivars [106,137,141].…”
Section: Discussionsupporting
confidence: 92%
“…In 'R18', 'R19', 'R23' and 'R30', the most elevated salt concentration (160 mM NaCl) generated the highest CAT activity, thus leading to improved protection against ROS in all the regenerated plants. This result agrees with previous reports, stating that many salt-tolerant species exhibited higher CAT activity, such as maize [136], sesame [137], potato [138], melon [139] and wheat [140]. Several earlier authors reported that salinity increased APX activity in many salt-tolerant cultivars [106,137,141].…”
Section: Discussionsupporting
confidence: 92%
“…Our research corroborates previous studies [47,48] had measured an enhanced activity of SOD, POD, and CAT in plants treated with a high NaCl dose and the activities of these enzymes were again higher in the two tolerant genotypes. Feki et al [66] and Koca et al [67] also demonstrated that tolerance to salinity in wheat and sesame genotypes was associated with lower MDA contents and higher activities of antioxidant enzymes. Thus, it is evident from our results and the results of others [10,68] that the higher POD, CAT, and APX activities coordinate with SOD activity to deal with the undesirable effect of O 2 − and H 2 O 2 and the activities of these enzymes are strongly correlated with tolerance to salt-induced oxidative stress in wheat and barley.…”
Section: Discussionmentioning
confidence: 99%
“…An enzymatic antioxidant system (SOD, POD, CAT, APX, GR AND GST) protects plants against oxidative damage of salinity [ 61 , 62 , 63 ] ( Figure 5 ). Zinc also resulted in increased antioxidant enzyme activities.…”
Section: Discussionmentioning
confidence: 99%